The Things That Really Matter Philosophical conversations on the cornerstones of life - Hauskeller, Michael (UCL Press, 2022)
While being rooted in the academic discourse, The Things That Really Matter comprehensively explores the most fundamental aspects of human life in an accessible, non-technical language, adding fresh perspectives and new arguments and considerations that are designed to stimulate further debate and, in some cases, a deliberate redirection of research interests in the respective areas. It features a series of conversations about the things in our life that we all, in one way or another, wrestle with if we are at all concerned about what kind of world we live in and what our role in it is: things like birth, age, and death, good and evil, the meaning of life, the nature of the self and the role the body plays for our identity, our gendered existence, love and faith, free will, beauty, and our experience of the sacred. Situating abstract ideas in concrete experience, The Things That Really Matter encourages the reader to participate in an open-ended dialogue involving a variety of thinkers with different backgrounds and orientations. Lively and accessible, it shows thinking as an open-ended process and a collaborative endeavour that benefits from talking to each other rather than against each other, featuring real conversations, where ideas are explored, tested, changed, and occasionally dropped. It is thinking in motion, personal yet universal.